Do you feel safe at home? A Critical Discourse Analysis of Tools Used in Medical Settings to Screen for Intimate Partner Violence - Marshall, Laura H. (Journal of family violence, 2024)
Purpose: To evaluate the language used in screening instruments employed by physicians and other health care providers to determine whether a patient is a victim of IPV. Method: We employed Critical Discourse Analysis, including a three-step iterative coding process, to analyze the language used in 40 text- and computer-based screening tools. Results: We found many screening tools contain language that may reinforce the power imbalance inherent in the physician–patient relationship through discourse that denies patient agency, echoes violent imagery with terms that are inherently violent themselves, and reduces the patient to a depersonalized object of a care provider’s actions. Conclusions: The choice of language used in screening instruments that guide physicians’ interactions with patients is crucial, particularly in evaluating patients for intimate partner violence. Violence between intimate partners can be exacerbated by an imbalance in power in a personal relationship. When language mimics that power imbalance in the exam room—a place where patients may already feel diminished agency—the potential arises that a patient will be reluctant to disclose IPV.